Killer on the road ; The babysitter lives [large type] - Jones, Stephen Graham, 1972- (Thorndike Press large print high octane., 2025)
"In The Babysitter Lives, when high school senior Charlotte agrees to babysit the Wilbanks twins, she plans to put the six-year-olds to bed early and spend a quiet night studying. But the house is filled with mysterious noises and soon Charlotte has to admit that every babysitter's worst nightmare has come true: they're not alone in the house. In The Killer on the Road, sixteen-year-old Harper has decided to run away from home. What she doesn't realize is that she has been marked by a very unique serial killer who's been trolling the highway for the past three years"--